Simulation studies of an overmoded RBWO under low guiding magnetic field - Reddy V.V.; Ansari M.A.; Thottappan M. (My University, 2025)
An overmoded sinusoidally corrugated Relativistic Backward Wave Oscillator (RBWO) has been designed and simulated for Gigawatt power level at low guiding magnetic field. In the upstream, a trapezoidal cavity resonant reflector (TRR) is used to reduce the over modulation of the electron beam. The applied DC voltage is 550 kV and the developed electron beam current is ∼5.9 kA under the guiding magnetic field 0.19 T. The Particle-in-Cell (PIC) simulation predicted an RF power of ∼0.97 GW at operating frequency ∼3.6 GHz with the corresponding power conversion efficiency of ∼30%. Further, the device is investigated for the cyclotron resonance absorption region near to pi-mode of operation. © 2019 IEEE.